2016
DOI: 10.1152/ajpendo.00370.2015
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial impairment induced by postnatal ActRIIB blockade does not alter function and energy status in exercising mouse glycolytic muscle in vivo

Abstract: -Because it leads to a rapid and massive muscle hypertrophy, postnatal blockade of the activin type IIB receptor (ActRIIB) is a promising therapeutic strategy for counteracting muscle wasting. However, the functional consequences remain very poorly documented in vivo. Here, we have investigated the impact of 8-wk ActRIIB blockade with soluble receptor (sActRIIB-Fc) on gastrocnemius muscle anatomy, energy metabolism, and force-generating capacity in wild-type mice, using totally noninvasive magnetic resonance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 59 publications
(90 reference statements)
0
15
0
Order By: Relevance
“…5). Although other studies of mouse models with muscle atrophy showed that soluble ActRIIB treatment increased absolute muscle contractile function of compromised muscle, 23,24,28,44 there were also reports of earlier muscle fatigability, 26,45 decreased gene expression of components involved in mitochondrial function and oxidative phosphorylation, 46,47 and reduced myofiberspecific function in mdx mice (mouse model of Duchenne muscular dystrophy) with treatment of higher concentrations of soluble ActRIIB. 25 Consistent with these studies, myostatin knockout (MSTN 2/2 ) mice exhibited centralized nuclei, a sign of muscle degeneration, and reduced relative muscle contractile function compared with WT and heterozygous myostatin-deficient (MSTN 1/2 ) littermates, 48 suggesting that a complete absence of myostatin is detrimental to muscle myofiber function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). Although other studies of mouse models with muscle atrophy showed that soluble ActRIIB treatment increased absolute muscle contractile function of compromised muscle, 23,24,28,44 there were also reports of earlier muscle fatigability, 26,45 decreased gene expression of components involved in mitochondrial function and oxidative phosphorylation, 46,47 and reduced myofiberspecific function in mdx mice (mouse model of Duchenne muscular dystrophy) with treatment of higher concentrations of soluble ActRIIB. 25 Consistent with these studies, myostatin knockout (MSTN 2/2 ) mice exhibited centralized nuclei, a sign of muscle degeneration, and reduced relative muscle contractile function compared with WT and heterozygous myostatin-deficient (MSTN 1/2 ) littermates, 48 suggesting that a complete absence of myostatin is detrimental to muscle myofiber function.…”
Section: Discussionmentioning
confidence: 99%
“…56 Several studies have raised concerns about impairment of mitochondrial function with myostatin inhibition. A limited group of studies in MSTN 2/2 mice demonstrated increased force production that was not proportional to their muscle hypertrophy, which may have reflected decreased mitochondrial function, [45][46][47]57 muscle fiber type switching, 57,58 deficits in oxidative metabolism that can lead to decreased endurance capacity, [57][58][59][60] and/or decreased capillary density in muscle that alters the aerobic metabolism. 58 Unlike MSTN 2/2 mice, Bechir and colleagues found that energy status and function of glycolytic muscles were not disturbed during 6-minute fatigue exercise with ActRIIB blockade in both WT and mdx mice.…”
Section: Discussionmentioning
confidence: 99%
“…This was unlikely in the present study for at least 2 reasons. First, we recently demonstrated that an 8‐week treatment with sActRIIB‐Fc does not affect fiber type distribution in the gastrocnemius muscle of wild‐type mice . Second, our methodology allows stimulation of the whole gastrocnemius muscle, and there is no reason that 1 type of fiber would be recruited more than the other in sActRIIB‐Fc‐treated animals compared with controls.…”
Section: Discussionmentioning
confidence: 97%
“…Shift in the pattern of fiber type recruitment and alteration of activation–relaxation processes have been proposed to explain the reduction of contractile ATP cost throughout a fatiguing exercise . Mouse gastrocnemius muscle is a mixed muscle composed mainly of fast glycolytic type‐2b fibers (about 85%) with low oxidative capacity; the remaining muscle is composed of fast‐oxidative type‐2a fibers with higher oxidative capacity . Because a fiber is more fatigue resistant and contracts more economically when its metabolism is oxidative, change in muscle typology and/or preferential recruitment of type‐2a fibers could explain the decrease in contractile ATP cost in fatigued muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation